The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.3390/s90503801
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current Methodologies for Regional Evapotranspiration Estimation from Remotely Sensed Data

Abstract: An overview of the commonly applied evapotranspiration (ET) models using remotely sensed data is given to provide insight into the estimation of ET on a regional scale from satellite data. Generally, these models vary greatly in inputs, main assumptions and accuracy of results, etc. Besides the generally used remotely sensed multi-spectral data from visible to thermal infrared bands, most remotely sensed ET models, from simplified equations models to the more complex physically based two-source energy balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
345
0
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 593 publications
(396 citation statements)
references
References 202 publications
3
345
0
10
Order By: Relevance
“…Some local differences occur unavoidably due to the inaccuracy of the various mathematical expressions used to compute a complex hydrological process such as ET. Remote sensing ET values reflect more the real world conditions as they are based on observations [33][34][35]42]. The agreement between SWAT and remote sensing data was expressed by means of the correlation coefficient and the bias.…”
Section: Resultsmentioning
confidence: 99%
“…Some local differences occur unavoidably due to the inaccuracy of the various mathematical expressions used to compute a complex hydrological process such as ET. Remote sensing ET values reflect more the real world conditions as they are based on observations [33][34][35]42]. The agreement between SWAT and remote sensing data was expressed by means of the correlation coefficient and the bias.…”
Section: Resultsmentioning
confidence: 99%
“…The use of surface energy balance algorithms based on remote sensing data has been shown to be quite promising for the estimation of actual evapotranspiration on both regional and local scales (LI et al, 2009). The Surface Energy Balance System (SEBS) model was proposed by SU (2002) to estimate atmospheric turbulent fluxes and evaporative fraction using satellite data and ancillary surface and meteorological information.…”
Section: Introductionmentioning
confidence: 99%
“…A Surface Energy Balance System (SEBS) for the estimation of atmospheric turbulent fluxes and surface evaporation using satellite earth observation data in the visible, near infra-red and thermal infrared frequency range has been designed for composite terrain with heterogeneous surfaces at a larger scale (Su, 2002). SEBS, applied to many case studies in Europe and Asia (Gokmen et al, 2012;Ma et al, 2014;Wang and Dickinson, 2012), has been shown as one of the most logical and accurate methods in ET estimation (Li et al, 2009). The accuracy of SEBS depends on the land surface physical parameters which is suitable to the study areas (Wood et al, 2003).…”
Section: Introductionmentioning
confidence: 99%